Development of Clinical Pharmacy Key Performance Indicators for Hospital Pharmacists Using a Modified Delphi Approach. (June 2015) - Fernandes, Olavo; Gorman, Sean K.; Slavik, Richard S.; Semchuk, William M.; Shalansky, Steve; Bussières, Jean-François; Doucette, Douglas; Bannerman, Heather; Lo, Jennifer; Shukla, Simone; Chan, Winnie W. Y.; Benninger, Natalie; et al.
Background: Key performance indicators (KPIs) are quantifiable measures of quality. There are no published, systematically derived clinical pharmacy KPIs (cpKPIs).Objective: A group of hospital pharmacists aimed to develop national cpKPIs to advance clinical pharmacy practice and improve patient care.Methods: A cpKPI working group established a cpKPI definition, 8 evidence-derived cpKPI critical activity areas, 26 candidate cpKPIs, and 11 cpKPI ideal attributes in addition to 1 overall consensus criterion. Twenty-six clinical pharmacists and hospital pharmacy leaders participated in an internet-based 3-round modified Delphi survey. Panelists rated 26 candidate cpKPIs using 11 cpKPI ideal attributes and 1 overall consensus criterion on a 9-point Likert scale. A meeting was facilitated between rounds 2 and 3 to debate the merits and wording of candidate cpKPIs. Consensus was reached if 75% or more of panelists assigned a score of 7 to 9 on the consensus criterion during the third Delphi round.Results: All panelists completed the 3 Delphi rounds, and 25/26 (96%) attended the meeting. Eight candidate cpKPIs met the consensus definition: (1) performing admission medication reconciliation (including best-possible medication history), (2) participating in interprofessional patient care rounds, (3) completing pharmaceutical care plans, (4) resolving drug therapy problems, (5) providing in-person disease and medication education to patients, (6) providing discharge patient medication education, (7) performing discharge medication reconciliation, and (8) providing bundled, proactive direct patient care activities.Conclusions: A Delphi panel of hospital pharmacists was successful in determining 8 consensus cpKPIs. Measurement and assessment of these cpKPIs will serve to advance clinical pharmacy practice and improve patient care.